2019
DOI: 10.1111/febs.14804
|View full text |Cite
|
Sign up to set email alerts
|

PtdIns(4,5)P2 is generated by a novel phosphatidylinositol 4‐phosphate 5‐kinase in the protist parasite Entamoeba histolytica

Abstract: Entamoeba histolytica is an intestinal protist parasite that causes amoebiasis, a major source of morbidity and mortality in developing countries. Phosphoinositides are involved in signalling systems that have a role in invasion and pathogenesis of this parasite. Phosphatidylinositol 4‐phosphate 5‐kinase (PIP5K) catalyses the generation of phosphatidylinositol(4,5)bisphosphate (PtdIns(4,5)P2), a key species of phosphoinositide that regulates various cellular processes. However, phosphatidylinositol phosphate k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…PIPK type I produces PI(3,4,5)P 3 from PI(4,5)P 2 . PI(4)P is produced from IP by the action of PI(4)K type III and also, PI can be phosphorylated to generate PI(3)P by class III PI3K (Sharma et al, 2019). Important advances in the lipid knowledge of E. histolytica constitute the findings focused on the inositol group.…”
Section: Pi and Phosphoinositides Synthesis And Metabolismmentioning
confidence: 99%
“…PIPK type I produces PI(3,4,5)P 3 from PI(4,5)P 2 . PI(4)P is produced from IP by the action of PI(4)K type III and also, PI can be phosphorylated to generate PI(3)P by class III PI3K (Sharma et al, 2019). Important advances in the lipid knowledge of E. histolytica constitute the findings focused on the inositol group.…”
Section: Pi and Phosphoinositides Synthesis And Metabolismmentioning
confidence: 99%
“…One reason for poor binding of SDS can be the recalcitrance of the protein to unfold under standard conditions of sample preparation for SDS-PAGE. A structurally ultra-stable protein derived from a hyperthermophile can fail to unfold within 2-3 min, or even hours, of boiling in standard SLB, or even under harsher conditions as reported for proteins from Pyrococcus furiosus [12][13][14][15]. (ii) High innate negative charge content.…”
Section: Underlying Causes Of Poor Sds Binding Leading To Non-trivialmentioning
confidence: 99%
“…Highly acidic proteins can be expected to repel SDS. In a recent series of papers examining the binding of SDS to proteins, it has been observed that the overall charged status of a protein is the primary determinant of the ease with which it can be approached by SDS molecules [1,13,16]. If the pH of a protein's environment is well below its pI, it protein possesses an overall positive charge, and is easily approached by SDS.…”
Section: Am-dre Shown By Highly Acidic Proteinsmentioning
confidence: 99%
“…The role of PtdIns(4,5)P 2 metabolism has not been studied in relation to processes involving actin cytoskeleton dynamics in E. histolytica . Out of the two members of PIPK family, type I and II that synthesise PtdIns(4,5)P 2 , only type I PIPK (EhPIPKI) is found in E. histolytica and has been recently characterised biochemically (Sharma, Bhattacharya, & Bhattacharya, ). Though EhPIPKI phosphorylates PtdIns(4)P generating PtdIns(4,5)P 2 , it is quite distinct in biochemical properties from PIPKs of other organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Though EhPIPKI phosphorylates PtdIns(4)P generating PtdIns(4,5)P 2 , it is quite distinct in biochemical properties from PIPKs of other organisms. EhPIPKI has high‐substrate specificity towards PtdIns(4)P, possesses a stretch of tandem repeat motifs in the central region of the kinase domain, and observed to undergo post‐translational cleavage in E. histolytica (Sharma et al, ) . Expression of EhPIPKI was found to be relatively high in phagocytic cell population as compared with the nonphagocytic population of cells (Sateriale et al, 2012).…”
Section: Introductionmentioning
confidence: 99%